Oxidation behavior of NiAl produced by gel combustion synthesis - Gonsalvez T.A.; Manap A.; Afandi N.; Misran H. (Trans Tech Publications Ltd, 2023)
Alumina; Aluminum alloys; Aluminum oxide; Binary alloys; Calcination; Oxidation; Scale (deposits); Calcination temperature; Elemental compositions; Energy dispersive spectrometry; Field emission scanning; Gel combustion synthesis; Isothermal oxidations; NiAl; Oxidation behaviors; Combustion synthesis